Construction of an EPO (Human-Erythropoietin) Synthetic Gene Through a Recurvise-PCR Method - Fuad, Asrul Muhamad; Gusdinar, Tutus; Retnoningrum, Debbie Sofie; Natalia, Dessy (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2008)
Human erythropoietin (hEPO) is an important glycoprotein in human that is coded by a single gene named EPO (eryhtopoietin). EPO is a glycoprotein hormone that promotes erythropoiesis, which is the formation process of mature red blood cell (erythrocytes) in human bodies. It is widely used for treatment of anemia in patient With chronic renal failure. Therefore EPO has been classified as hematopoietic cytokine. Recombinant hEPO (rhEPO) has been commercially available, such a Epogen. It is produced in mammalian cell, such as CHO (Chine e hamster ovary) cells for the reason of its complex structure as a glyco-protein. In an effort to use and optimize heterolgous EPO gene expression in an alternative eukaryotic host cells such as yeast, an EPOsynthetic gene (EPOsyn) was constructed. The synthetic gene had been designed to contain optimaI Pichiapastoris codon usage . It had been constructed by a recursive-PCR method in two-step PCR reactions. The gene was assembled from 8 single strands synthetic oligonuclotides having an average length of 90 nt with 20 to 30 overlap region between two adjacent oligos. The synthetic gene has less GC content (4-.3 1%) compared its native (human) gene (59.08%). The synthetic gene has been cloned in pCR2.1 cloning plasmid and sequenced. From 8 independent clones, it was revealed that the error rate was 1.59%, in which 1.42% was due to deletions and 0.17% due to substitutions. Design of the gene sequences, construction method and DNA sequence analysis of the gene will be discussed in this paper. Keywords: Human erythropoietin (hEPO), erythropoiesis EPOsynthetic gene, recursive-PCR, Pichiapastoris, hematopoietic cytokine.